Adolescence in Art (and psychoanalysis): school projects - Maria Cristina Poli; Katia Regina Faissol (Universidade Federal do Rio Grande do Sul, 2016)
This paper discusses the process of becoming an adolescent in the contemporary world through the lens of psychoanalysis, from a work in a federal public school in the city of Rio de Janeiro. We based our intervention with teenagers on the presentation of the projects Múltiplas Vozes (Multiple Voices) and Refazer (Re-do), giving them the opportunity to expand the symbolic universe in which they live through the encounter with some artistic expressions. This way, the opportunities to unveil new ways on creating new social bonds in the process of insertion in the adult world are expanded.